Graphene battery slurry, preparation method thereof and graphene battery

By using graphene-based ternary composite materials and graphene oxide-coated aminated silica microspheres in graphene batteries, the problem of insufficient thermal stability of existing graphene batteries is solved, and excellent rate performance is achieved. Cycling performance and thermal stability.

CN119447288APending Publication Date: 2025-02-14JIESHOU HUAYU POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619377.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing graphene batteries have poor thermal stability in high temperature environments and are greatly affected by regions and seasons, resulting in insufficient rate performance, cycling performance and thermal stability.

Method used

Graphene-based ternary composite material and graphene oxide-coated amino-silica microspheres are prepared by ultrasonic dispersion and high-speed mixing to form a battery material with excellent conductivity and heat resistance. .

Benefits of technology

The rate performance, cycle performance and thermal stability of graphene batteries are significantly improved, making the battery perform more stably in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133047030000071
    Figure BDA0005133047030000071
  • Figure BDA0005133047030000081
    Figure BDA0005133047030000081
Patent Text Reader

Abstract

The invention discloses graphene battery slurry, a preparation method thereof and a graphene battery, and belongs to the technical field of batteries. The preparation method of the graphene battery slurry comprises the following steps: S1, mixing a graphene-based ternary composite material, graphene oxide coated aminated silicon dioxide microspheres, a dispersing agent and N-methyl pyrrolidone, and performing uniform ultrasonic dispersion to obtain a mixed solution; and S2, adding polyvinylidene fluoride into the mixed solution, and mixing in a high-speed mixer to obtain the graphene battery slurry. The graphene-based ternary composite material prepared from the graphene, the nitrogen-doped carbon nanotubes and the conductive carbon black is applied to the graphene battery slurry, and the silicon dioxide microspheres are added into the slurry, so that the prepared slurry has excellent conductivity and heat resistance; the obtained graphene battery has excellent rate capability, cycle performance and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a graphene battery slurry and a preparation method thereof, and a graphene battery. Background Art

[0002] Battery slurry is an important component of the battery, and its quality and performance affect the actual use of the battery. Graphene is a two-dimensional material composed of a single layer of carbon atoms, in which the carbon atoms are arranged in a honeycomb lattice. The honeycomb structure of graphene is very stable. The electrons inside graphene are also very little disturbed, the electrons move fast, and the resistivity is lower than that of copper and silver, making it the material with the lowest resistivity at present. Therefore, only a small amount of addition is needed to improve the conductivity of the battery slurry.

[0003] Graphene is directly added in the process of preparing battery slurry, and the graphene conductive slurry is mixed with active materials, coated and made into electrodes. Graphene dispersed between active materials can form a continuous and efficient conductive network. Compared with the "point-to-point" contact mode constructed by traditional graphite conductive agents, graphene dispersed in electrodes can form a "point-to-surface" contact mode with electrode materials, providing a long-range and fast conduction path for electrons, which is equivalent to increasing the content of electrode active substances, thereby increasing the discharge capacity of the electrode.

[0004] Graphene contacts the electrode material in a "point-to-surface" manner in the electrode, but when large flakes of graphene are added in large amounts, it will hinder the transport of lithium ions and enhance the polarization effect. Coupled with cost factors, this limits the application of graphene conductive materials. The graphene batteries currently commonly used on the market have the advantages of high efficiency, environmental protection, and safety. However, graphene batteries are greatly affected by regions and seasons, and often have problems such as poor thermal stability in high temperature environments. Summary of the invention

[0005] The purpose of the present invention is to provide a graphene battery slurry and a preparation method thereof and a graphene battery, to prepare a graphene battery slurry with excellent conductivity and heat resistance, so that the obtained graphene battery has excellent rate performance and cycle performance and thermal stability.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] In a first aspect, the present invention provides a graphene battery slurry, comprising the following raw materials in parts by weight:

[0008] 4-6 parts of graphene-based ternary composite material, 2-4 parts of amino-modified silica microspheres coated with graphene oxide, 0.1-0.2 parts of dispersant, 2-4 parts of polyvinylidene fluoride, and 92-96 parts of N-methylpyrrolidone.

[0009] Furthermore, the dispersant is one of polyvinyl pyrrolidone, polypyrrole and polyvinyl alcohol.

[0010] In a second aspect, the present invention provides a method for preparing a graphene battery slurry, comprising the following steps:

[0011] S1, mixing the graphene-based ternary composite material, the graphene oxide-coated amino-modified silica microspheres, the dispersant and N-methylpyrrolidone, and uniformly dispersing them by ultrasonication to obtain a mixed solution;

[0012] S2. Add polyvinylidene fluoride to the mixed solution, and mix in a high-speed mixer for 1-3 hours to obtain a graphene battery slurry.

[0013] Furthermore, the rotation speed of the high-speed mixer is 800-1000r / min.

[0014] Further, the graphene-based ternary composite material described in S1 is prepared by the following steps:

[0015] Graphene and nitrogen-doped carbon nanotubes are added to deionized water, and conductive carbon black is added after ultrasonic dispersion for 1-2 hours. The ultrasonic dispersion is continued with mechanical stirring for 1-2 hours, and the dispersed mixed solution is reacted at 170-180°C for 8-10 hours. After the reaction is completed, the graphene-based ternary composite material is obtained by filtration and drying.

[0016] Furthermore, the mass ratio of the graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1-2:1:1-2.

[0017] Further, the graphene oxide-coated aminated silica microspheres described in S1 are prepared by the following steps:

[0018] The aminated silica microspheres are added into the ethanol dispersion of graphene oxide, stirred, allowed to stand, filtered, washed and dried to obtain the aminated silica microspheres coated with graphene oxide.

[0019] Furthermore, the mass ratio of the amino-treated silica microspheres to the graphene oxide is 4:1.

[0020] Furthermore, the amino-containing silica microspheres are prepared by the following steps:

[0021] KH550 and ethanol are prepared into a 2% KH550 solution by mass, and silica microspheres are added to the solution. After ultrasonic treatment for 0.5-1h, the solution is heated to 70-80°C for reaction for 8-10h, filtered and dried to obtain amino silica microspheres.

[0022] Furthermore, the size of the silica microspheres is 1-10 μm;

[0023] The dosage of KH550 is 2%-6% of the mass of silica microspheres.

[0024] In a third aspect, the present invention provides a graphene battery, including the graphene battery slurry prepared by the present invention.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention utilizes graphene, nitrogen-doped carbon nanotubes and conductive carbon black to prepare a graphene-based ternary composite material with excellent conductive properties, and the graphene-based ternary composite material is used in a graphene battery slurry, and the resulting battery has excellent rate performance and cycle performance.

[0027] (2) The present invention adds graphene oxide-coated amino-containing silica microspheres to the graphene battery slurry. The graphene oxide layer gives the silica microspheres good conductivity and good compatibility with graphene. The silica microspheres can promote the dispersion of flaky graphene and improve the heat resistance of the battery slurry, thereby improving the thermal stability of the battery. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a graphene battery slurry, comprising the following raw materials in parts by weight:

[0031] 4 parts of graphene-based ternary composite material, 2 parts of amino-modified silica microspheres coated with graphene oxide, 0.1 parts of polyvinyl pyrrolidone, 3 parts of polyvinylidene fluoride, and 94 parts of N-methylpyrrolidone.

[0032] Prepared by the following steps:

[0033] (1) Preparation of graphene-based ternary composite materials:

[0034] Graphene and nitrogen-doped carbon nanotubes were added to deionized water, and conductive carbon black was added after ultrasonic dispersion for 1 hour. The mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black was 1:1:2. Ultrasonic dispersion was continued with mechanical stirring for 1 hour. The dispersed mixed solution was reacted at 180° C. for 10 hours. After the reaction was completed, the graphene-based ternary composite material was obtained by filtering and drying.

[0035] (2) Preparation of graphene oxide-coated aminated silica microspheres:

[0036] 1) KH550 and ethanol are prepared into a 2% KH550 solution, and silica microspheres with a size of 1-10 μm are added to the solution, and the amount of KH550 is 4% of the mass of the silica microspheres. After ultrasonication for 0.5 h, it is heated to 80° C. and reacted for 10 h, filtered, and dried to obtain amino silica microspheres;

[0037] 2) adding the aminated silica microspheres to the ethanol dispersion of graphene oxide, wherein the mass ratio of the aminated silica microspheres to the graphene oxide is 4:1, stirring, standing, filtering, washing, and drying to obtain graphene oxide-coated aminated silica microspheres.

[0038] (3) mixing the graphene-based ternary composite material, the graphene oxide-coated amino-modified silica microspheres, polyvinyl pyrrolidone and N-methyl pyrrolidone, and uniformly dispersing them by ultrasonication to obtain a mixed solution;

[0039] (4) Add polyvinylidene fluoride to the mixed solution, and mix in a high-speed mixer at a rotation speed of 1000 r / min for 2 h to obtain a graphene battery slurry.

[0040] Example 2

[0041] The present embodiment is different from the embodiment 1 in that the “mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:2” in step (1) is changed to “mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:1”; the remaining raw materials and preparation process remain the same as those in the embodiment 1.

[0042] Example 3

[0043] The present embodiment is different from the embodiment 1 in that the “mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:2” in step (1) is changed to “mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 2:1:1”; the remaining raw materials and preparation process remain the same as those in the embodiment 1.

[0044] Example 4

[0045] Compared with Example 2, this embodiment differs in that "4 parts of graphene-based ternary composite material, 2 parts of amino-treated silica microspheres coated with graphene oxide" is changed to "5 parts of graphene-based ternary composite material, 3 parts of amino-treated silica microspheres coated with graphene oxide"; the remaining raw materials and preparation process remain the same as in Example 2.

[0046] Example 5

[0047] Compared with Example 2, this embodiment differs in that "4 parts of graphene-based ternary composite material, 2 parts of amino-treated silica microspheres coated with graphene oxide" is changed to "6 parts of graphene-based ternary composite material, 4 parts of amino-treated silica microspheres coated with graphene oxide"; the remaining raw materials and preparation process remain the same as in Example 2.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that the preparation process of step (1) is changed to: graphene, nitrogen-doped carbon nanotubes and conductive carbon black are mixed in a mass ratio of 1:1:2 to obtain a mixed material, and the mixed material is used to replace the "graphene-based ternary composite material" in the raw material; the remaining raw materials and preparation process remain the same as in Example 1.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that no graphene oxide-coated amino-containing silica microspheres are added to the graphene battery slurry; the remaining raw materials and preparation process remain the same as those in Example 1.

[0052] Comparative Example 3

[0053] Compared with Example 1, the difference between this comparative example and this comparative example is that the mixed material prepared in Comparative Example 1 is used in the graphene battery slurry to replace the "graphene-based ternary composite material" in the raw material, and no amino-treated silica microspheres coated with graphene oxide are added; the other raw materials and preparation process remain the same as those in Example 1.

[0054] Comparative Example 4

[0055] The difference between this comparative example and Example 1 is that the "mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:2" in step (1) is changed to "the mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:4"; the remaining raw materials and preparation process remain the same as in Example 1.

[0056] Comparative Example 5

[0057] The difference between this comparative example and Example 1 is that the "mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 1:1:2" in step (1) is changed to "the mass ratio of graphene, nitrogen-doped carbon nanotubes and conductive carbon black is 4:1:1"; the remaining raw materials and preparation process remain the same as in Example 1.

[0058] Comparative Example 6

[0059] The present comparative example is different from Example 1 in that the preparation process of step (1) is changed to: adding graphene and nitrogen-doped carbon nanotubes into deionized water with a mass ratio of graphene to nitrogen-doped carbon nanotubes of 1:1, continuing ultrasonic dispersion combined with mechanical stirring for 1 hour, reacting the dispersed mixed solution at 180° C. for 10 hours, and after the reaction, filtering and drying to obtain a graphene-based binary composite material; replacing the “graphene-based ternary composite material” in the raw material with the “graphene-based binary composite material”; and the remaining raw materials and preparation process remain the same as those in Example 1.

[0060] Comparative Example 7

[0061] The present comparative example is different from Example 1 in that the preparation process of step (1) is changed to: adding graphene and conductive carbon black into deionized water with a mass ratio of graphene to conductive carbon black of 1:2, continuing ultrasonic dispersion combined with mechanical stirring for 1 hour, reacting the dispersed mixed solution at 180° C. for 10 hours, and after the reaction, filtering and drying to obtain a graphene-based binary composite material; replacing the “graphene-based ternary composite material” in the raw material with the “graphene-based binary composite material”; and the remaining raw materials and preparation process remain the same as those in Example 1.

[0062] Comparative Example 8

[0063] Compared with Example 1, the difference in this comparative example is that "graphene" is used to replace the "graphene-based ternary composite material" in the raw material; the other raw materials and preparation process remain the same as those in Example 1.

[0064] The graphene battery slurry prepared in Examples 1 to 5 and Comparative Examples 1 to 8 was mixed with lithium iron phosphate in a mass ratio of 90:10, and a positive electrode sheet was prepared through coating, rolling, slitting, and sheeting. The negative electrode slurry was prepared by mixing graphite, carbon black, a thickener (sodium carboxymethyl cellulose), and a binder (styrene-butadiene rubber) in a mass ratio of 95:1:1:3 for the counter electrode, and the negative electrode sheet was prepared from the slurry through the same process. The diaphragm was a 16 μm thick porous polyethylene film. 1 mol / L lithium hexafluorophosphate was used as the electrolyte. The positive electrode sheet, the negative electrode sheet, the diaphragm, and the electrolyte were assembled into a graphene battery for performance testing.

[0065] At 25°C and in the voltage range of 2.0-3.8V, the discharge capacity of the battery at different rates was tested, and the results are shown in Table 1. At 25°C and 50°C and in the voltage range of 2.0-3.8V, the battery was subjected to charge and discharge cycle tests, and the discharge capacity of the battery was tested at 1C rate for 100 cycles, and the capacity retention rate was calculated. The results are shown in Table 2:

[0066] Table 1

[0067]

[0068]

[0069] Table 2

[0070] Capacity retention rate (%) 25℃, 1C cycle 100 times 50℃, 1C cycle 100 times Example 1 95.3 94.8 Example 2 96.5 96.0 Example 3 95.5 95.0 Example 4 97.4 97.2 Example 5 98.5 98.3 Comparative Example 1 86.8 86.3 Comparative Example 2 93.1 82.7 Comparative Example 3 83.4 73.0 Comparative Example 4 89.3 88.8 Comparative Example 5 86.5 86.0 Comparative Example 6 78.5 78.0 Comparative Example 7 79.2 78.8 Comparative Example 8 77.5 77.0

[0071] It can be seen from Table 1 that the batteries prepared in Examples 1 to 5 all have excellent rate performance and cycle performance; compared with Example 1, Example 2 and Example 3, it can be seen that appropriately increasing the proportion of graphene in the graphene-based ternary composite material within a certain range helps to improve the conductivity of the battery slurry, and can improve the rate performance and cycle performance of the battery.

[0072] Compared with Example 2, Example 4 and Example 5, increasing the proportion of graphene-based ternary composite material and graphene oxide-coated amino-modified silica microspheres in the graphene battery slurry is beneficial to improving the rate performance, cycle performance and thermal stability of the battery.

[0073] Compared with Example 1, Comparative Example 1 shows that the graphene-based ternary composite material in the graphene battery slurry is replaced by a mixed material obtained by directly mixing graphene, nitrogen-doped carbon nanotubes and conductive carbon black, and the rate performance and cycle performance of the obtained battery are poor; Compared with Example 1, Comparative Example 2 shows that no amino-treated silica microspheres coated with graphene oxide are added to the graphene battery slurry, and the thermal stability of the obtained battery is poor; Compared with Comparative Example 3, Comparative Example 1 and Comparative Example 2, the graphene-based ternary composite material in the graphene battery slurry is replaced by a mixed material obtained by directly mixing graphene, nitrogen-doped carbon nanotubes and conductive carbon black, and no amino-treated silica microspheres coated with graphene oxide are added, and the battery rate performance, cycle performance and thermal stability are the worst.

[0074] Comparing Comparative Example 4 with Example 1, it is found that a too low proportion of graphene in the graphene-based ternary composite material is not conducive to improving the rate performance and cycle performance of the battery; comparing Comparative Example 5 with Example 1, it is found that a too high proportion of graphene will lead to capacity decay at high rates; only a suitable proportion can prepare a graphene-based ternary composite material with excellent conductive properties.

[0075] Compared with Example 1, Comparative Examples 6, 7 and 8 show that the batteries obtained by using graphene-based binary composite materials or graphene instead of graphene-based ternary composite materials in the battery slurry have lower rate performance and cycle performance, indicating that the graphene-based ternary composite materials have excellent conductivity.

[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A graphene battery slurry, characterized in that: The invention comprises the following raw materials in parts by weight: 4-6 parts of graphene-based ternary composite material, 2-4 parts of graphene oxide-coated amino-modified silica microspheres, 0.1-0.2 parts of dispersant, 2-4 parts of polyvinylidene fluoride, and 92-96 parts of N-methylpyrrolidone; The graphene-based ternary composite material is a composite of graphene, nitrogen-doped carbon nanotubes and conductive carbon black.

2. A graphene battery slurry according to claim 1, characterized in that: The dispersant is one of polyvinyl pyrrolidone, polypyrrole and polyvinyl alcohol.

3. A method for preparing a graphene battery slurry according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, mixing the graphene-based ternary composite material, the graphene oxide-coated amino-modified silica microspheres, the dispersant and N-methylpyrrolidone, and uniformly dispersing them by ultrasonication to obtain a mixed solution; S2. Add polyvinylidene fluoride into the mixed solution and mix to obtain graphene battery slurry.

4. The method for preparing a graphene battery slurry according to claim 3, characterized in that: The graphene-based ternary composite material described in S1 was prepared by the following steps: Graphene and nitrogen-doped carbon nanotubes are added to deionized water, and conductive carbon black is added after ultrasonic dispersion for 1-2 hours. The ultrasonic dispersion is continued with mechanical stirring for 1-2 hours, and the dispersed mixed solution is reacted at 170-180°C for 8-10 hours. After the reaction is completed, the graphene-based ternary composite material is obtained by filtration and drying.

5. The method for preparing a graphene battery slurry according to claim 4, characterized in that: The mass ratio of the graphene, the nitrogen-doped carbon nanotubes and the conductive carbon black is 1-2:1:1-2.

6. The method for preparing a graphene battery slurry according to claim 3, characterized in that: The graphene oxide-coated aminated silica microspheres described in S1 were prepared by the following steps: The aminated silica microspheres are added into the ethanol dispersion of graphene oxide, stirred, allowed to stand, filtered, washed and dried to obtain the graphene oxide-coated silica microspheres.

7. The method for preparing a graphene battery slurry according to claim 6, characterized in that: The mass ratio of the amino-modified silica microspheres to graphene oxide is 4:

1.

8. The method for preparing a graphene battery slurry according to claim 6, characterized in that: The amino silica microspheres are prepared by the following steps: Add silica microspheres to the KH550 solution, sonicate for 0.5-1h, heat to 70-80°C, react for 8-10h, filter, and dry to obtain amino silica microspheres.

9. The method for preparing a graphene battery slurry according to claim 8, characterized in that: The size of the silica microspheres is 1-10 μm; The dosage of KH550 is 2%-6% of the mass of silica microspheres.

10. A graphene battery, characterized in that: The invention comprises the graphene battery slurry as described in claims 1-2.